EFFECTIVENESS OF MACEDONIAN ANTI-CORRUPTION LEGISLATİON AND IMPLEMENTATION GAPS - Slamkov, Gjorgi (International Scientific Journal Vision, 2025)
The paper addresses a crucial issue in the fight against corruption, which is whether anti-corruption legislation is effectively implemented in practice. The author has conducted an analysis of the implementation of several essential competencies of the State Commission for the Prevention of Corruption, as well as data from competent institutions on persons convicted of corruption crimes. The paper emphasizes that North Macedonia has a generally good legal framework for the fight against corruption, but weak implementation, which has also been noted in reports by international organizations, is a fundamental problem for the proper fight against corruption. The author pays special attention to the level of implementation of the strategic document for the fight against corruption - the National Strategy and the consequences of the poor implementation of this document. The paper uses the method of content analysis, as well as the statistical method. In addition, official data from competent institutions were used. Strengthening the fight against corruption is a prerequisite for the rule of law and in this direction it is necessary for the competent institutions to take action to fully implement their competencies, which implies normative and institutional changes in order to achieve effective implementation of the regulation.